2017
DOI: 10.1016/j.jtho.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Driven by Mutations: The Predictive Value of Mutation Subtype in EGFR -Mutated Non–Small Cell Lung Cancer

Abstract: EGFR-mutated NSCLC is a genetically heterogeneous disease that includes more than 200 distinct mutations. The implications of mutational subtype for both prognostic and predictive value are being increasingly understood. Although the most common EGFR mutations-exon 19 deletions or L858R mutations-predict sensitivity to EGFR tyrosine kinase inhibitors (TKIs), it is now being recognized that outcomes may be improved in patients with exon 19 deletions. Additionally, 10% of patients will have an uncommon EGFR muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
155
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(166 citation statements)
references
References 84 publications
3
155
0
3
Order By: Relevance
“…The most common sensitive (classic) EGFR mutations are in‐frame deletions in exon 19 (19del) and exon 21 substitution of leucine for arginine (L858R) . Other uncommon sensitive (non‐classical) mutations have also been detected, including G719X, L861Q, 19 insertions, A763_Y764 insFQEA, and S768I mutations …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common sensitive (classic) EGFR mutations are in‐frame deletions in exon 19 (19del) and exon 21 substitution of leucine for arginine (L858R) . Other uncommon sensitive (non‐classical) mutations have also been detected, including G719X, L861Q, 19 insertions, A763_Y764 insFQEA, and S768I mutations …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Other uncommon sensitive (non-classical) mutations have also been detected, including G719X, L861Q, 19 insertions, A763_Y764 insFQEA, and S768I mutations. [8][9][10][11][12] Afatinib is an oral irreversibly-binding ErbB family blocker that can effectively block signaling from EGFR (ErbB1), HER2/ErbB2, ErbB4, and all relevant ErbB family members. 13,14 The LUX-Lung 3 and 6 trials revealed that first-line treatment with afatinib significantly prolongs the progression-free survival (PFS) of patients with common or uncommon sensitive EGFR mutations compared to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The exon 19 deletion (del19) and the L858R point mutation of exon 21 are two classic types of TKI‐sensitive mutations. Some mutation types, such as the 20 exon insertion, are resistant to TKIs of all generations . Thus, identification of the EGFR mutation type is helpful for accurate selection of TKIs.…”
Section: Introductionmentioning
confidence: 99%
“…Some mutation types, such as the 20 exon insertion, are resistant to TKIs of all generations. 6 Thus, identification of the EGFR mutation type is helpful for accurate selection of TKIs. It is challenging to obtain sufficient tissue for mutation analysis in clinical work.…”
Section: Introductionmentioning
confidence: 99%
“…1 Aberrant activation of EGFR is among the most common oncogenic driving events in human cancer, which is mediated largely through different classes of genomic alterations within the EGFR gene. 2 These genomic events include somatic EGFR mutations within regions of either the extracellular domain, in glioblastoma, or the kinase domain in lung adenocarcinoma, 3,4 as well as through gene amplification as observed in many other types of solid tumors. 5,6 In addition, several intragenic deletions within either the extracellular or C-terminal domain of EGFR have also been reported to be oncogenic in a subset of glioblastoma and lung adenocarcinoma.…”
mentioning
confidence: 99%